Pharmacotherapy as a fall risk factor - Ivana Bóriková; Martina Tomagová; Katarína Žiaková; Michaela Miertová (University of Ostrava, 2018)
Aim: To determine the correlation between pharmacotherapy and high risk of fall based on the Morse Fall Scale (MFS score ≥ 45) in acute and long-term care settings. Design: A quantitative cross-sectional descriptive correlation study. Methods: The study was conducted at a University Hospital in Martin (UHM) and a selected long-term care facility (LTC) in Martin (Slovakia) June-October 2016. The pharmacotherapeutic data were obtained from the health documentation of the respondents. The fall risk was assessed by using the MFS screening tool within 24-48 hours of admission to the facility. Results: For the group of UHM patients (n = 63), the mean MFS score for fall risk was high (60.6 ± 22.4), and the correlation (p = 0.030) between the number of medications administered in 24 hours and high risk of fall was significant. For the group of LTC patients (n = 89), the mean MFS score for fall risk was moderate (35.4 ± 15.9). The correlations were not significant. Conclusion: Pharmacotherapy is an important fall risk factor; therefore, it is necessary to determine it within the assessment of overall fall risk. The risk management of pharmacotherapy is an effective and important multifactorial intervention in programmes of fall prevention in acute and long-term care. Keywords: fall, hospital, long-term care, Morse Fall Scale, pharmacotherapy, screening, senior.